FLT3 expression initiates in fully multipotent mouse hematopoietic progenitor cells. - Buza-Vidas, N; Woll, P; Hultquist, A; Duarte, S; Lutteropp, M; Bouriez-Jones, T; Ferry, H; Luc, S; Jacobsen, SE (2011)
Lymphoid-primed multipotent progenitors with down-regulated megakaryocyte-erythroid (MkE) potential are restricted to cells with high levels of cell-surface FLT3 expression, whereas HSCs and MkE progenitors lack detectable cell-surface FLT3. These findings are compatible with FLT3 cell-surface expression not being detectable in the fully multipotent stem/progenitor cell compartment in mice. If so, this process could be distinct from human hematopoiesis, in which FLT3 already is expressed in multipotent stem/progenitor cells. The expression pattern of Flt3 (mRNA) and FLT3 (protein) in multipotent progenitors is of considerable relevance for mouse models in which prognostically important Flt3 mutations are expressed under control of the endogenous mouse Flt3 promoter. Herein, we demonstrate that mouse Flt3 expression initiates in fully multipotent progenitors because in addition to lymphoid and granulocyte-monocyte progenitors, FLT3(-) Mk- and E-restricted downstream progenitors are also highly labeled when Flt3-Cre fate mapping is applied.